Heterogeneity, state dependence and health - Timothy J. Halliday (Institute for the Study of Labor (IZA), 2008)
We investigate the evolution of health over the life-cycle. We allow for two sources of persistence: unobserved heterogeneity and state dependence. Estimation indicates that there is a large degree of heterogeneity. For half the population, there are modest degrees of state dependence. For the other half of the population, the degree of state dependence is near unity. However, this may be the result of a high frequency of people in our data who never exit healthy states, potentially resulting in a failure to pin down the state dependence parameter for this segment of the population. We conclude that individual characteristics that trace back to early adulthood and before can have far reaching effects on health.
urn:nbn:de:101:1-20080421202
Keywords: I1; 360; Health; dynamic panel data models; gradient; Gesundheit; Gesundheitsversorgung; Panel; USA